TS-1 zeolite as an effective diffusion barrier for highly stable Pd membrane supported on macroporous alpha-Al2O3 tube - Wang, X.; Tan, X.; Meng, B.; Zhang, X.; Liang, Q.; Pan, H.; Liu, Shaomin (Royal Society of Chemistry, 2013)
Thin and defect-free supported palladium membranes were prepared on macroporous α-alumina ceramic tubes using TS-1 zeolite as the intermediate and diffusion barrier layer. It is necessary to modify the pore size of the substrate and form an effective diffusion barrier between the palladium membrane and the support in order to obtain a continuous and thin Pd layer. The detailed microstructure of the composite membranes were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) spectroscopy. Pd membranes supported on a TS-1 layer with a thickness of 2–5 μm showed high H2 flux and ideal selectivity of H2/N2 in the working temperature range. The result reveals that the palladium penetrated into the TS-1 films through the nonzeolitic pores existing in the zeolite films. The resultant Pd-TS-1 membrane displays very high stability due to the excellent anchorage of Pd layer inside the zeolite barrier grown on the support. This membrane could be able to tolerate rapid and repeated cycling of gases, temperature and pressure without sacrificing its good permeance and selectivity, even below the Pd embrittlement temperature (<573 K). These results suggest that TS-1 zeolite is an effective intermediate substrate modifier to bridge the large pore size of the support for the synthesis of a thin Pd layer.